Delayed inputs of hot 137Cs and 241Am particles from Chernobyl to sediments from three Finnish lakes: implications for sediment dating - Appleby, Peter G.; Piliposyan, Gor; Weckström, Jan; Piliposian, Gayane (Journal of paleolimnology, 2023)
Anomalous peaks in the 137 Cs and 241 Am records from three lake sediment cores from southern Finland appear to be due to the presence of micron-size hot radioactive particles, almost certainly originating in fallout from the 1986 Chernobyl accident. Since the imbedding sediments all post-date 1986 by several decades, it appears that they were initially deposited on the catchments of these lakes and transported to the lakes some years later. The activities of the particles were determined using a sequential splitting process. Two of the particles were found to contain 137 Cs with activities of 64 ± 4 mBq and 266 ± 15 mBq respectively. The third contained 241 Am with an activity of 17 ± 2 mBq, but no evidence of significant amounts of 137 Cs. The delayed input of such particles into the sedimentary records highlights the need for care in using 137 Cs or 241 Am as chronostratigraphic markers in areas subject to significant levels of contamination from Chernobyl fallout.